2007
DOI: 10.1038/sj.bjc.6603615
|View full text |Cite
|
Sign up to set email alerts
|

Impact of differential cyclin D1 expression and localisation in prostate cancer

Abstract: Cyclin D1 is a critical regulator of androgen-dependent transcription and cell cycle progression in prostate cancer cells. Despite the influence of D-type cyclins on prostate cancer proliferation, few studies have examined the expression of cyclin D1 in localised tumours or challenged its relevance to disease progression. Cyclin D1 status was characterised using immunohistochemistry in 38 non-neoplastic prostate samples, 138 primary human prostate carcinomas, and three lymph node metastatic specimens. Relevanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
58
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 85 publications
13
58
4
Order By: Relevance
“…Here, we showed that cyclin D3 localization is largely cytoplasmic in low-grade tumors and as tumor grade increases, total cyclin D3 expression is diminished. This profile is distinct from recent analyses of cyclin D1 expression, where although a large fraction of tumors score negative for cyclin D1, increased cytoplasmic expression was observed in a subset of tumors, and some nuclear expression is noted in higher grades (Comstock et al, 2007). Total cyclin D3 expression is inversely correlated with Ki-67, whereas nuclear cyclin D1 corresponds with higher Ki-67.…”
Section: Cyclin D3 Expression Is Altered In Pca Progressioncontrasting
confidence: 86%
See 2 more Smart Citations
“…Here, we showed that cyclin D3 localization is largely cytoplasmic in low-grade tumors and as tumor grade increases, total cyclin D3 expression is diminished. This profile is distinct from recent analyses of cyclin D1 expression, where although a large fraction of tumors score negative for cyclin D1, increased cytoplasmic expression was observed in a subset of tumors, and some nuclear expression is noted in higher grades (Comstock et al, 2007). Total cyclin D3 expression is inversely correlated with Ki-67, whereas nuclear cyclin D1 corresponds with higher Ki-67.…”
Section: Cyclin D3 Expression Is Altered In Pca Progressioncontrasting
confidence: 86%
“…Hematoxylin and eosin staining, immunohistochemical staining for cyclin D3 and Ki-67, scoring, analyses and images were performed as previously described (Wetherill et al, 2006;Comstock et al, 2007).…”
Section: Histologymentioning
confidence: 99%
See 1 more Smart Citation
“…[31][32][33] Disruption in this process has been associated with unchecked AR activity and has been found to occur at multiple levels in human tumors. [34][35][36] In addition, CDK6 negates the ability of cyclin D1 to suppress AR function, and can serve to heighten AR activity independent of it skinase function. 37 In G 2 , CDK1 activity has been shown to promote AR phosphorylation and stabilization, resulting in increased AR activity.…”
Section: Ar-mediated Cell Cycle Progressionmentioning
confidence: 99%
“…SPARC in prostate cancer N Said et al positive correlation with prostate cancer metastasis (Comstock et al, 2007). Conversely, upregulation of p21 Cip and/or p27 Kip inhibits the activity of most cyclin/ cyclin-dependent kinase complexes, causing growth inhibition in prostate cancer (Roy et al, 2007).…”
Section: Discussionmentioning
confidence: 99%